MSMES Marketing Strategies Of Batik Malangan In The Covid19 Pandemic - Nova Dwi HERNANIK; Sudarmiatin SUDARMIATIN; Agus HERMAWAN (Indonesia Strategic Sustainability, 2022)
Economic activity must grow and develop faster than the growth in the number of people looking for work. One closely related element to economic growth is MSMEs, namely micro, small and medium enterprises.Indonesia's wealth assets that can be used as objects of batik tourism are also used as Indonesian cultural identity to the world. It is the reason that attracts researchers to make Batik Blimbing Malang SMEs the research object. Currently, the main task of Batik Blimbing Malang that must be carried out as a batik industry that is sufficiently developed to maintain the viability of its business in the situation of the COVID-19 pandemic era, is one of them by designing appropriate promotional strategies to face market competition. Therefore, this study aims to explore the sales promotion strategy of SMEs by conducting a qualitative research approach. This study was conducted on Batik Blimbing Malang. The results showed that the strategy of Batik Blimbing Malang in maintaining its business continuity, among others, was to do several points, including: Advertising, Personal selling, Sales promotion, Public relations, Word of mouth, Customer relationship.